Aromatic aldehyde functionalized polycaprolactone and polystyrene macromonomers: synthesis, characterization and aldehyde-aminooxy click reaction - Sane, Prakash S.; Tawade, Bhausaheb V.; Palaskar, Dnyaneshwar V.; Menon, Shamal K.; Wadgaonkar, Prakash P. (Reactive & Functional Polymers, 2012)
New bis-aldehyde functionalized initiators, viz, 4,4'-(4,4'-(5-hydroxypentane-2,2-diyl)bis(4,1-phenylene))bis(oxy)dibenza ldehyde (1) and 4,4'-bis(4-(4-(formylphenoxy) phenyl) pentyl 2-bromopropanoate (2) were synthesized starting from commercially available 4,4'-bis(4-hydroxyphenyl) pentanoic acid. These initiators were utilized, respectively, for ring opening polymerization of E-caprolactone and atom transfer radical polymerization of styrene. Well-defined polycaprolactone macromonomers (M-n(GPC): 2600-19400, PDI: 1.37-1.47) and polystyrene macromonomers (M-n(GPC): 2800-28200, PDI: 1.11-1.16) with bis-aldehyde functionality were synthesized. The kinetic study of styrene polymerization showed controlled polymerization behaviour. The presence of aldehyde functionality in macromonomers was confirmed by H-1 NMR spectroscopy. The reactivity of aldehyde functionality was demonstrated by carrying out aldehyde-aminooxy click reaction of polycaprolactone macromonomer with O-(2-azidoethyl) hydroxylamine which proceeded in a quantitative manner without backbone degradation. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Aldehyde-terminated macromonomers; ATRP; Polycaprolactone; Polystyrene; ROP